Bifeprunox: Efficacy with Minimal Metabolic Concerns - Cunningham, Muriel (MD Conference Express, 2007)
Bifeprunox, a partial dopamine agonist, is being developed as a possible treatment for schizophrenia. The results of a 6-month randomized, double-blind, placebo-controlled study of 497 patients with schizophrenia.